Effect of Principal Cutting Edge Angle of High-Speed Steel Tools On The Machining Stability of Aluminium 6061 During Turning - Nanang Kosim; Imran; Burhan Hafid (International Journal of Science and Environment (IJSE), 2026)
The turning process is one of the most widely used machining operations to produce workpieces with the required dimensions and surface quality. The stability of the turning process is influenced by several machining parameters, one of which is the principal cutting edge angle (κr) of the cutting tool. Variations in the principal cutting edge angle affect the distribution of cutting forces, vibration characteristics, and machining stability. This study aims to analyze the effect of principal cutting edge angle variations of High-Speed Steel (HSS) cutting tools on the stability of the turning process of Aluminium 6061. The experiment was conducted using a conventional lathe with three principal cutting edge angle variations, namely 45°, 60°, and 90°. Other machining parameters, including spindle speed, feed rate, depth of cut, workpiece material, and cutting tool material, were maintained constant throughout the experiment. Machining stability was evaluated based on vibration measurements using a vibration meter, and each experimental condition was repeated three times. The experimental data were analyzed using One-Way Analysis of Variance (ANOVA). The results indicated that the average vibration values for κr angles of 45°, 60°, and 90° were 0.933 mm/s, 0.740 mm/s, and 0.743 mm/s, respectively. Statistical analysis showed a significant effect of principal cutting edge angle variation on vibration level (F = 50.82, p < 0.05). Among the tested angles, the 60° principal cutting edge angle produced the lowest vibration level, indicating the highest turning process stability. These findings demonstrate that selecting an appropriate principal cutting edge angle can improve machining stability and optimize turning performance for Aluminium 6061.